ANALISIS TINGKAT RISIKO ERGONOMI PADA AKTIVITAS MACHINING DI PT X PLANT JAKARTA - Istiqomah Suryaningtyas; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
PT X is a remanufacturing company of heavy equipment which can not be separated from mechanical activities of material or product manually. Handling of material manually such as lowering, pushing, pulling, carrying, the use of mechanical tools and bending can cause injuries or occupational diseases. This handling not only heavy materials but also in light and small materials when repeated, incorrect duration and position it can also cause injury, illness or occupational accident. This injury is known as a disorder of the musculoskeletal system of musculoskeletal disorders (MSD’S). The purpose of this research is to analyze the level of ergonomic risk in machining activity at PT X plant Jakarta. This research is a descriptive research with cross sectional study approach. Based on the result of this research was known that 50% of machining activity has high ergonomic risk level on valve lifting process, up skir process, down skir process and grinding valve process with risk level between 8 – 10. Subsequently, 50% has medium ergonomic risk level on the phase of turning, taking sandpaper, setting up sandpaperand grinding crank shaft with risk level between 4 – 6. Moreover, the duration of the machining activity is 50% with long duration, 13% with moderate duration and 37% with short duration. And the perceived complaints on machining activity about 100% complained of stiff and numb in neck, 66,67% complained of stiff in the leg and 33,33% complained of back pain.